Spatial-temporal trends of rainfall, maximum and minimum temperatures over west Africa - Muthoni, F. (Institute of Electrical and Electronics Engineers, 2020)
This article investigates the magnitude and significance of spatial-temporal trends of 37 years' time series of the gridded data for rainfall, maximum (Tmax) and minimum (Tmin) temperature for West Africa. A modified Mann-Kendall test and Theil-Sen's slope estimator were utilized to test the significance and the magnitude of trends, respectively. The magnitude of significant trends for three variables between six agroecological zones (AEZs) was compared. Gridded climate data represented gauge data with high accuracy and, therefore, can reliably complement the sparse observation network in West Africa. The three variables showed significant positive and negative trends of varying magnitude and spatial extent. June to September rainfall showed a positive increase (0.1-5 mm/month/year) that mostly occurred north of 11° latitude. October rainfall showed a positive trend across the region, but the magnitude was higher south of the same latitude. A widespread significant warming trend was observed across all AEZs and months. However, a localized cooling in August and September over the Sahel and Sudan Savanna was an exception. The cooling over the two AEZs coincided with a positive trend of rainfall. The zonal analysis revealed that the magnitude of the positive trend of June, September, and October rain increased following a North-South gradient from the Sahel to humid forest AEZs. Results provide spatial evidence of climate change in a limited data environment to guide the targeting of appropriate adaptation measures. The information generated from this article helps the design of early warning systems against droughts and floods.